1994
DOI: 10.1113/expphysiol.1994.sp003778
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ryanodine on the contraction of isolated frog atrial trabeculae is triggered by caffeine

Abstract: SUMMARYRyanodine is without effect on the contraction of frog atrial muscle when applied alone. However, if agents which bring about Ca2+ release from the sarcoplasmic reticulum (SR), e.g. caffeine, hypertonic fluid or rapid cooling, are applied together with or up to 1 h after exposure to ryanodine, subsequent effects upon contraction are evident. These include a complete inhibition of the contractures evoked by caffeine, rapid cooling or hypertonic solutions applied in Na+-deficient media and a shift in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…As in both skeletal muscle and rat ventricle fibres the SR provides a cellular store for calcium that is responsible for the activation of contraction, it is reasonable that, assuming the SR in the frog heart to have the same function, a much smaller capacity for this purpose exists in these heart cells. However, even though most, if not all, of the Ca 2+ required for the activation of the twitch tension in frog heart cells is supplied by the inward Ca 2+ current through the surface membrane (Niedergerke et al 1976, Tunstall & Chapman 1994, atrial and ventricular cells may rely on Ca 2+ release from the SR under special conditions, such as adrenergic and/or P2 purinergic stimulation (Niedergerke & Page 1981).…”
Section: Sarcoplasmic Reticulummentioning
confidence: 99%
“…As in both skeletal muscle and rat ventricle fibres the SR provides a cellular store for calcium that is responsible for the activation of contraction, it is reasonable that, assuming the SR in the frog heart to have the same function, a much smaller capacity for this purpose exists in these heart cells. However, even though most, if not all, of the Ca 2+ required for the activation of the twitch tension in frog heart cells is supplied by the inward Ca 2+ current through the surface membrane (Niedergerke et al 1976, Tunstall & Chapman 1994, atrial and ventricular cells may rely on Ca 2+ release from the SR under special conditions, such as adrenergic and/or P2 purinergic stimulation (Niedergerke & Page 1981).…”
Section: Sarcoplasmic Reticulummentioning
confidence: 99%
“…In the ventricle of rat heart, the SR is quite abundant and block of the SR Ca 21 pump by thapsigargin, resulting in depletion of the SR Ca 21 stores, reduces twitch tension and Ca 21 transients by 80% (Inesi et al, 1998). At the other end of the spectrum, frog myocardium relies on extracellular Ca 21 , SR Ca 21 release is of small magnitude and its role in e-c coupling has been debated (Kavaler, 1974;Anderson et al, 1977;Niedergerke et al, 1976;Niedergerke and Page, 1981a,b;Morad and Cleemann, 1987;Tunstall and Chapman, 1994). Indeed, it is thought that SR Ca 21 in frog myocardium is called into play only under conditions of adrenergic and/or P 2 purinergic stimulation (Niedergerke and Page, 1981b).…”
Section: Introductionmentioning
confidence: 99%
“…In ventricle, on the other hand, the effect of caffeine is either absent (Niedergerke and Page, 1981a) or very small (Chapman and Miller, 1974), and the latter may be attributable to a direct effect on the myofibrils at the high concentrations of caffeine used (S. Page, personal communication; see also Wendt and Stephenson, 1983). In frog atrium ryanodine leads to a transient increase in twitch tension if applied in the presence of caffeine, but seems to have no effect in its absence (Tunstall and Chapman, 1994). No effect of ryanodine was reported for the ventricle, even though a large range of concentrations was used (Ciofalo, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this finding, voltage‐clamp studies of frog ventricle showed that the Ca 2+ involved in the activation of tension arose primarily from the extracellular space 26 . Subsequently, studies in frog atrial cells using ryanodine and caffeine suggested that some Ca 2+ was stored in and capable of being released from the SR 27 . Nevertheless, the prevalent view remains that, in amphibian heart tissue, the SR is not a major source of Ca 2+ during the normal contraction 22 …”
Section: Is Sr In the Amphibian Pacemaker Cell Capable Of Releasing Cmentioning
confidence: 89%